ECG CHEST BAND FOR ARRHYTHMIA DETECTION AND BIOMETRIC EHR ACCESS - K, Karthika; Santhosh S; B, Ramani; L, Prathap (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Wearable ECG devices are valuable for heart patients monitoring systems and for fitness tracking and continuous health monitoring for individuals with no heart problems. Current devices are big, and the average person cannot afford them, which is why electronic health records need to be kept so that the ECG signal is integrated to the electronic health record. Keeping this in mind, our purpose is to make a wearable ECG device that is a lot smaller and cheaper than most devices while keeping the ECG signal intact and having smooth integration with electronic health records (EHR). Furthermore, in this case, to elicit the desired health outcome for the target population, which is all ages, we focus on health record usability, data security, and record management.